Inhibitory effect of 13 taxane diterpenoids from Chinese yew (Taxus chinensis var. mairei) on the proliferation of HeLa cervical cancer cells. Issue 10 (2nd October 2016) - Liu, Hai-Sheng; Gao, Yu-Huan; Liu, Li-Hong; Liu, Wei; Shi, Qing-Wen; Dong, Mei; Suzuki, Toshikazu; Kiyota, Hiromasa
Abstract: The inhibitory effect of 13 taxanes isolated from the Chinese yew ( Taxus chinensis var. mairei ) on the proliferation of human cervical cancer HeLa cells were examined using an MTT assay. Four compounds having a hydrophobic cinnamate side chain showed antiproliferative activity, which may be due to increased cell permeability.